Neural Biomarker Prospectively Predicts Increases in Anxiety Symptoms in Children After Hurricane Sandy - Meyer, Alexandria (J Am Acad Child Adolesc Psychiatry, 2017)
OBJECTIVE: Although most people will experience a traumatic event, only some will develop significant psychological symptoms in the aftermath. In the current study, we utilize a preexisting longitudinal study located in Long Island to examine the impact of Hurricane Sandy on internalizing symptoms in a large sample of children. We focused on temperamental fear and a biomarker of risk for anxiety, the error-related negativity (ERN). The ERN is a negative deflection in the event-related potential (ERP) occurring when individuals make mistakes and is increased in anxious individuals. METHOD: The final sample consisted of 223 children who had undergone an observational assessment of fear at age 3 and an electroencephalogram assessment of the ERN at age 6. At the age 9 assessment, internalizing symptoms were assessed, and then again after the hurricane (approximately 65 weeks later). RESULTS: A significant three-way interaction between fearfulness, hurricane stressors, and the ERN in predicting post-hurricane increases in internalizing symptoms suggested that children who were high in fear at age 3 and experienced elevated hurricane stressors were characterized by subsequent increases in internalizing symptoms, but only when they were also characterized by an increased ERN at age 6. CONCLUSION: These findings support a diathesis-stress model, suggesting that early temperament and pre-stressor biological markers confer risk for increased psychological symptoms following environmental stressors.